2011
DOI: 10.1371/journal.pone.0023363
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegenerative Properties of Chronic Pain: Cognitive Decline in Patients with Chronic Pancreatitis

Abstract: Chronic pain has been associated with impaired cognitive function. We examined cognitive performance in patients with severe chronic pancreatitis pain. We explored the following factors for their contribution to observed cognitive deficits: pain duration, comorbidity (depression, sleep disturbance), use of opioids, and premorbid alcohol abuse. The cognitive profiles of 16 patients with severe pain due to chronic pancreatitis were determined using an extensive neuropsychological test battery. Data from three co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 59 publications
3
39
0
Order By: Relevance
“…The malnutrition which occurs as a result of EPI can be associated with a deterioration in brain function. Acute pancreatitis is often associated with encephalopathy (Zhang & Tian, 2007), whilst chronic pancreatitis is accompinied with ascending cognitive decline (Jongsma et al, 2011). Close monitoring of the operated pigs in the present study (during the development of EPI) revealed no signs of the pigs experiencing any pain or loss of appetite.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…The malnutrition which occurs as a result of EPI can be associated with a deterioration in brain function. Acute pancreatitis is often associated with encephalopathy (Zhang & Tian, 2007), whilst chronic pancreatitis is accompinied with ascending cognitive decline (Jongsma et al, 2011). Close monitoring of the operated pigs in the present study (during the development of EPI) revealed no signs of the pigs experiencing any pain or loss of appetite.…”
Section: Discussionmentioning
confidence: 41%
“…Pancreatic insufficiency is often associated with marked neurological alterations related to cognitive and sensory motor function (Jongsma et al, 2011). Many patients with chronic pancreatitis report symptoms that are associated with a decrease in cognitive function, such as depressive symptoms (Gallassi, Morreale, & Pagni, 2001;Gomez et al, 2006;Oosterman, Derksen, van Wijck, Veldhuijzen, & Kessels, 2011), sleep disturbances (Goel, Rao, Durmer, & Dinges, 2009) and the use of opioid medication (Sjogren, Thomsen, & Olsen, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…We found that reactive inhibition was faster during and immediately after anodal tDCS relative to sham. attention-deficit hyperactivity disorder (ADHD; Aron and Poldrack 2005;Barkley 1997; Rubia et al 2001), schizophrenia (Enticott et al 2008;Kiehl et al 2000), obsessivecompulsive disorder and trichotillomania (Bohne et al 2008;Menzies et al 2007;Penadés et al 2007), Tourette syndrome (Ziemann et al 1997), chronic pain (Glass et al 2011;Jongsma et al 2011;Veldhuijzen et al 2012) and developmental stuttering (Eggers et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Among these complaints, memory is one of the most common and consistent (Epker & Ogden, 2013). Other factors, such as pain intensity and pain duration, have been shown to be positively correlated with objective measures of retrospective memory impairment in patients complaining of chronic orthopedic pain (Jongsma et al, 2011; Kreitler & Niv, 2007). However, severity of pain-related impairment is questionable.…”
mentioning
confidence: 99%